2007
DOI: 10.1073/pnas.0609149104
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42 GTPase-activating protein deficiency promotes genomic instability and premature aging-like phenotypes

Abstract: Cdc42 is a member of the Rho GTPase family known to regulate cell actin cytoskeleton organization, polarity, and growth, but its function in mammalian organismal physiology remains unclear. We found that natural aging of WT mice is marked with increased Cdc42 activity in various tissues. Among the negative regulators of Cdc42, gene targeting of Cdc42 GTPase-activating protein (Cdc42GAP) results in constitutively elevated Cdc42-GTP level in diverse tissues of adult mice; significantly shortened life span of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
109
0
7

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(125 citation statements)
references
References 35 publications
9
109
0
7
Order By: Relevance
“…The current Cdc42 conditional knockout model reveals unique HSC regulatory functions of Cdc42 that are not predictable in the Cdc42 gain-of-activity Cdc42GAP Ϫ/Ϫ mice (13,23,24). Although Cdc42GAP Ϫ/Ϫ hematopoietic progenitors show normal cell cycle progression but increased apoptosis due to increased JNK activity, Cdc42 Ϫ/Ϫ HSCs display drastically increased cell cycle progression/entry but unaltered survival property.…”
Section: Resultsmentioning
confidence: 99%
“…The current Cdc42 conditional knockout model reveals unique HSC regulatory functions of Cdc42 that are not predictable in the Cdc42 gain-of-activity Cdc42GAP Ϫ/Ϫ mice (13,23,24). Although Cdc42GAP Ϫ/Ϫ hematopoietic progenitors show normal cell cycle progression but increased apoptosis due to increased JNK activity, Cdc42 Ϫ/Ϫ HSCs display drastically increased cell cycle progression/entry but unaltered survival property.…”
Section: Resultsmentioning
confidence: 99%
“…ARHGAP1 codes for a Rho GTPase-activating protein 1, also known as Cdc42 GTPase-activating protein. It was shown that CDC42GAP-null mice also develop a senescence phenotype (Wang et al 2007). …”
Section: Pleiotropymentioning
confidence: 99%
“…However, in recent years a number of papers have appeared, particularly those involving prematurely aging mouse models, that implicate p53 in the regulation of some aging phenotypes (Lim et al, 2000;Tyner et al, 2002;Cao et al, 2003;Wong et al, 2003;Maier et al, 2004;Varela et al, 2005;Baker et al, 2006;Wang et al, 2007). In 2002, our laboratory described a genetically engineered mutant p53 mouse model (p53+/m) that exhibited an enhanced resistance to cancer that was accompanied by reduced longevity and premature onset of a number of aging phenotypes (Tyner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%